2017
DOI: 10.3184/146867816x14799161258479
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Adsorption of Carbon Monoxide on Cobalt Surfaces: A Dft Study

Abstract: The theoretical molecular adsorption energies, vibrational frequencies and total density of states of carbon monoxide (CO) on the (100), (110) and (111) surfaces of the face-centred cubic (FCC) crystalline phase of metallic cobalt were investigated using density functional theory calculations. The on-top adsorption state and three surface coverages were used for comparison of the results. The geometries of cobalt FCC surfaces, as well as those with adsorbed CO molecules and the CO binding energies were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…C 2 H 4 Li complex can adsorb maximum three CO, four CO 2 , four NO, two NO 2 , three SO, and three SO 2 molecules and the optimized structures are shown in Figure . Adsorption of maximum number of CO and CO 2 molecule on Li metal surface can be useful for the study of catalytic oxidation of CO molecule and hydrogenation of CO . These reactions play an important role in syngas production, water–gas shift production and Fischer–Tropsch process .…”
Section: Resultsmentioning
confidence: 99%
“…C 2 H 4 Li complex can adsorb maximum three CO, four CO 2 , four NO, two NO 2 , three SO, and three SO 2 molecules and the optimized structures are shown in Figure . Adsorption of maximum number of CO and CO 2 molecule on Li metal surface can be useful for the study of catalytic oxidation of CO molecule and hydrogenation of CO . These reactions play an important role in syngas production, water–gas shift production and Fischer–Tropsch process .…”
Section: Resultsmentioning
confidence: 99%
“…In the catalytic process, both CO and alkene molecules are commonly adsorbed onto adjacent Co atom sites to facilitate hydrogenation and C–C coupling reactions. However, traditional metallic Co catalysts typically exhibit a nearly uniform Co–Co localized symmetry structure, leading to identical charge distributions between neighboring Co atom sites (a nonpolar domain). This characteristic causes a strong dipole–dipole repulsive force between the adsorbed species, hindering the adsorption and activation of reactants and intermediates. Meanwhile, the insertion of CO into alkenes, which is the rate-determining step, becomes challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt is generally preferred over Fe and Ru for FTS as it possesses high activity and selectivity in the production of long-chain hydrocarbons from syngas [45][46][47][48]. Ge et al [30] reported a density functional theory study which was used to analyze the first steps in the mechanism of Fischer-Tropsch synthesis, i.e., CO 24}, low-coverage pathways with activation energies that lie below the energy of gas-phase CO were identified.…”
Section: Introductionmentioning
confidence: 99%